Application of various creep analysis methods for estimating the time-dependent behavior of cracked concrete beams. (June 2020) - Zhang, Sen; Hamed, Ehab
Abstract: A structural model is developed to predict the time-dependent behavior of cracked reinforced and partially prestressed concrete beams. The model considers creep, shrinkage, cracking, prestress relaxation and temperature. Three different methods to model the effect of creep are presented and compared, which include the effective modulus method, integral-type and rate-type formulations. The effect of temperature on both the creep and shrinkage is considered. A smeared cracking model is adopted and an iterative procedure is implemented at each time step to determine the cracked rigidities which vary through the length of the beam. The governing equations are solved using the multiple-shooting method at each time step. The validity of the proposed model is demonstrated through comparison to experimental data available in the literature. It was found that all three analysis methods provide equally reasonable prediction of the long-term behavior. A numerical study is also presented to demonstrate the capability of the model in simulating the time variation of stresses and strains in cracked concrete beams.